Fast surfing for availability or deep diving into quality - motivation and information seeking among middle and high school students - Jannica Heinstrom (Information Research: An International Electronic Journal)
Introduction. Information literacy education is central for students as a building block for functioning citizenship in an information rich world. To support students' development of information skills we need an awareness of underlying factors behind information seeking habits. This article will discuss whether differences in middle and high school students' information seeking may relate to their approaches to studying. Method. The sample consisted of 574 students, grades 6 to 12, who independently sought information in order to learn about a curriculum topic. Data were collected at three stages of the students' information seeking process with use of four survey instruments, including an adapted version of the ASSIST test. Analysis. The analysis of the ASSIST test and the structured questions was quantitative. The open questions were coded through an axial coding process and analysed qualitatively. Results. Students with different study approaches tended to focus on different information seeking aspects in addition to shared commonalities. Students with a surface approach prioritized easily available sources, deep students were aware of quality aspects, and strategic students organized and structured their searches. Conclusion. The search patterns resemble information seeking styles found in previous research. Level of engagement in the search task seems to be highly influential on information seeking behaviour.